Carrots and sticks as incentive mechanisms for the optimal initiation of insolvency proceedings - Jaka Cepec; Mitja Kovač (DANUBE: Law, Economics and Social Issues Review, 2016)
The pursuit of ex-ante efficiency in bankruptcy law has been widely discussed in recent law and economics literature. However, the exact incentive mechanisms inducing the optimal commencement of bankruptcy proceedings have generally been exempted from the current scholarly debate. Using the law and economics tools and comparative analysis, this paper seeks to identify insolvency-specific optimal incentive mechanisms, while using the general theory on carrots and sticks in legal regulations. The paper suggests the employment of mixed-sticks-and-carrots incentive mechanisms for managers' prompt proposals of insolvency proceedings as an optimal regulatory response. Moreover, the article provides comparative evidence that exclusive use of sticks or carrots in French, German, US, English, and Slovenian legal systems results in sub-optimal initiation of insolvency proceedings and may also induce adverse effects on prompt initiation.
Keywords: 330; Corporate Insolvency; Trigger Mechanisms; Incentives; Efficiency; Comparative Insolvency Law; Carrots and Sticks